PROBLEMATICS OF CHANGES IN MINING AND BANK PROVISIONS IN MINING LICENSING AUTHORITY - Probojati Bayu Herlambang; Rio Aldino Yosevan Silalahi; Sultoni Fikri (Jurnal Meta-Yuridis, 2023)
Problems with changing the policy of the Coal Mineral Law, regarding changes to permits, have resulted in some disharmony between the regional government and the central government. This writing was carried out with a focus on writing regarding mining licensing authority with reference to the Minerba Law with Law Number 3 of 2020. The purpose of this research is to evaluate the disharmony of minerba mining licensing policies by the central government towards regional governments. The method used in this research is normative juridical. In conducting research, the author obtains information by digging, finding out and finding a legal principle, rule of law, and legal doctrine which will be used in the future to answer several existing legal issues. The problem with changing policies regarding mining permits is because there are several substantive articles in the law which have logical consequences for the regional autonomy management sector. The takeover of mining licensing affairs by the central government "Centralization" has consequences, namely the reduced function of the state's right to control over the mineral and coal mining sector in regional governments, both provincial and district/city. The centralization carried out by the government is a way of simplifying mining business licensing, so that in this case the central government aims to make policies regarding management and licensing easier